Endothelial nitric oxide synthase levels and their response to exercise in patients with slow coronary flow - Taşolar, Hakan (Clinics Cardive Publishing, 2013)
BACKGROUND: Endothelial dysfunction plays a key role in the aetiopathogenesis of slow coronary flow (SCF) even if there is no obstructive epicardial lesion. Reduced plasma levels of endothelial nitric oxide synthase (eNOS) are an important indicator of endothelial dysfunction. We aimed to determine plasma levels of eNOS and their relationship with exercise in patients with SCF. METHODS: Twenty-two patients with SCF in at least one coronary artery and 17 healthy individuals were included in this study. The TIMI frame count method was used to determine SCF. Plasma levels of eNOS before and after effort were determined in the patient and control groups. RESULTS: Basal eNOS levels in the patient group were lower than in the control group (p = 0.040), and plasma eNOS levels after exercise decreased more significantly in the patient group compared to the control group (p = 0.002). Median decreases of eNOS in response to exercise were higher in the SCF group than in the control group (p < 0.001), and the decrease observed in the control group was not statistically significant (p = 0.35). There were significantly negative correlations between TIMI frame count and plasma levels of eNOS at baseline and after exercise (r = –0.51, p = 0.015, r = –0.58, p = 0.005, respectively). Moreover, there was also a positive correlation between the rate–pressure product and plasma levels of eNOS after exercise in patients with SCF (r = 0.494, p = 0.019). CONCLUSION: Our findings indicate an important pathophysiological relationship between the severity of SCF in which endothelial dysfunction plays a role in its pathogenesis and the level of circulating plasma levels of eNOS.